1986
DOI: 10.1042/bj2400789
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the photolytic breakdown of hydroperoxides and peroxidized fatty acids by using electron spin resonance spectroscopy. Spin trapping of alkoxyl and peroxyl radicals in organic solvents

Abstract: Spin trapping using 5,5-dimethyl-1-pyrroline N-oxide (DMPO) has been used to detect and distinguish between the carbon-centred, alkoxyl, and peroxyl radicals produced during the photolytic decomposition of hydroperoxides. Photolysis of tert-butyl and cumene hydroperoxides, and peroxidized fatty acids, in toluene, with low levels of u.v. light, is shown to lead to the initial production of alkoxyl radicals by homolysis of the oxygen-oxygen bond. Subsequent reaction of these radicals with excess hydroperoxide le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 22 publications
5
45
1
1
Order By: Relevance
“…Reaction of this spin trap with superoxide and hydroxyl radicals or radicals of a lipid nature derived from hydroxyl radicals produces spin-trapped adducts with characteristic EPR spectra (5,6). Moreover, spin trapping using DMPO has been used to detect and distinguish between carbon-centered, alkoxyl, and peroxyl radicals produced during metal ion-and lipoxygenase-catalyzed breakdown (7), as well as photolytic breakdown of peroxidized fatty acids (8).…”
mentioning
confidence: 99%
“…Reaction of this spin trap with superoxide and hydroxyl radicals or radicals of a lipid nature derived from hydroxyl radicals produces spin-trapped adducts with characteristic EPR spectra (5,6). Moreover, spin trapping using DMPO has been used to detect and distinguish between carbon-centered, alkoxyl, and peroxyl radicals produced during metal ion-and lipoxygenase-catalyzed breakdown (7), as well as photolytic breakdown of peroxidized fatty acids (8).…”
mentioning
confidence: 99%
“…The sulfur analogues of alkoxyl radicals (thiyls) are also trapped at fast rate constants (-lo8 M-I s-' ) (13). spin trapping studies have suggested that oxygen-centered radicals may be important intermediates in radiolysis (14) and sonolysis (15) reactions, ozone-related chemistry (16,17), xanthinelxanthine oxidase systems (18), carcinogenesis (19), antitumour drug redox interactions (20)(21)(22), cigarette smoke (23), druglskin phototoxicity (24,25), neutrophil action (26a-c), peroxidation reactions (27)(28)(29)(30)(31), as well as myocardial ischemia/reperfusion injury (32a-c).…”
mentioning
confidence: 99%
“…b) The tate of formation of the spin trapping adducts with 4-POBN approached to zero when the reaction approximated anaerobiosis, c) No spectrum appeared in the presence of 4-POBN when the mixture was bubbled with nitrogen p¡ to the addition of fipoxygenase. It is apparent that they did not consid~r the fact that lipoxygenase is not active without oxygen or hydroperoxyl linoleic acid [14,17].…”
Section: Resultsmentioning
confidence: 99%
“…Rosen claimed that MNPOL-LOO was not stable as well [1]. Davies et al have trapped LOO" with DMPO produced from photolysis of hydroperoxides at room temperamre [17]. But Merritt et al have shown that the DMPO-LOO, if formed, were unstabte even at -80~ from the Pb(OAc)4-ROOH reaction [18].…”
Section: Resultsmentioning
confidence: 99%